2019
DOI: 10.1002/pon.5161
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the psychological impact of active surveillance or active treatment in newly diagnosed favorable‐risk prostate cancer patients: A 9‐month longitudinal study

Abstract: Objective This study aimed to explore the psychological impact of favorable‐risk prostate cancer (PCa) and associated treatment (active surveillance [AS] or active treatment [AT]), comparing prevalence and temporal variability of generalized anxiety, PCa‐specific anxiety, and depression symptoms. Methods PCa patients were recruited at diagnosis prior to treatment decision‐making and completed questionnaires assessing anxiety (State‐Trait Anxiety Inventory short form [STAI‐6] and Memorial Anxiety Scale for Pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Unmet emotional/psychological needs were reflected in men's fears/worries associated with cancer, feelings of uncertainty in relation to AS and unmet information needs, and the accessibility of appropriate support groups/resources specific to men on AS. While research comparing men on AS with men who have received curative PCa treatment generally show that depression and anxiety are comparable and scores decrease over time, recent research suggests anxiety may be higher in men on AS. In line with this recent research, the present analysis suggests some men may be inadequately supported psychologically/emotionally.…”
Section: Resultsmentioning
confidence: 99%
“…Unmet emotional/psychological needs were reflected in men's fears/worries associated with cancer, feelings of uncertainty in relation to AS and unmet information needs, and the accessibility of appropriate support groups/resources specific to men on AS. While research comparing men on AS with men who have received curative PCa treatment generally show that depression and anxiety are comparable and scores decrease over time, recent research suggests anxiety may be higher in men on AS. In line with this recent research, the present analysis suggests some men may be inadequately supported psychologically/emotionally.…”
Section: Resultsmentioning
confidence: 99%
“…[41] One study prospectively measuring anxiety for 9 months has found higher levels of distress among men on AS than those on AT, which was attributed to men being followed at a center without a strong focus on AS. [42] The absence of anxiety expressed by our contemporary cohort suggests that the benefits of AS are being appreciated while the potential risks are being minimized. Other studies have shown that men made lifestyle changes, including undertaking complementary and alternative medicine treatments, to help them cope with the stress of having an untreated cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps this is due to a perceived inactivity of active surveillance relative to traditional narratives of cancer treatment. Therefore, the authors suggest a need to improve diagnosis and treatment information provision particularly for lower risk patients 7 …”
Section: Discussionmentioning
confidence: 99%